Nonlinear Fracture Mechanics: Volume I Time-Dependent Fracture 1988
DOI: 10.1520/stp26779s
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Loading Rate on the Deformation and Ductile Fracture of A533B Steel at 70C

Abstract: Many engineering materials exhibit rate- or time-dependent inelastic deformation. This phenomenon is generally associated with the strain rate sensitivity of the flow stress. The main objective of the work described in this paper is to examine the influence of loading rate on the deformation and ductile fracture of a reactor pressure vessel steel, A533B Class 1, at 70C. The reported experimental work is in three parts, examining the behavior of (1) uniaxial specimens, (2) small-scale notched ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…For sustained load conditions in A533B steel Smith and Garwood [8] found that if yielding is contained ductile crack growth would diminish. However, the present results for @-titanium under sustained loading and in contained yielding, particularly for CT specimen L5, crack growth continues until eventual failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For sustained load conditions in A533B steel Smith and Garwood [8] found that if yielding is contained ductile crack growth would diminish. However, the present results for @-titanium under sustained loading and in contained yielding, particularly for CT specimen L5, crack growth continues until eventual failure.…”
Section: Discussionmentioning
confidence: 99%
“…For the carbon-manganese steel it was shown there was a loading rate effect on the R-curve, but for the A533B steel there was no significant effect. Smith and Garwood [8] conducted further work on A533B steel and found that there were marginally different R-curves in terms of J and CTOD for different loading rates provided that the tests were conducted under clip gauge displacement rate control.…”
Section: Introductionmentioning
confidence: 99%
“…Krempl and Kallianpur [35], Garwood [36], Ingham and Morland [37], among others (see [36]) have clearly demonstrated this phenomenon for a number of engineering materials. Little, Krempl and Shih [38] have also carried out finite element analyses examining the stress and strain states near a crack tip for the small scale yielding problem.…”
Section: Introductionmentioning
confidence: 95%
“…Under sustained loading, time‐dependent deformation and crack growth can occur in ductile ferritic and austenitic steels at temperatures well below the conventional creep range 1–7 . However, failure is generally found to occur only if the sustained loads are close to the monotonic collapse load 7 .…”
Section: Introductionmentioning
confidence: 99%
“…In bodies containing defects, the appropriate stress is the so‐called reference stress, a measure of the overall level of plasticity within the body, which controls the crack‐tip stress and strain fields within the J ‐estimation approach 9 underlying R6. Time‐dependent plasticity or ‘cold creep’ has been attributed to the sensitivity of the material's stress–strain curve to loading rate, 1,2 and R6 advises that sustained load effects need only be considered at susceptible temperatures, currently considered to be below 200 °C in austenitic steel. The effect of limited crack extension on the integrity of a structure needs to be carefully assessed within the susceptible range.…”
Section: Introductionmentioning
confidence: 99%